Qinggan Huoxue Recipe Alleviates Alcoholic Liver Injury by Suppressing Endoplasmic Reticulum Stress Through LXR-LPCAT3 - Lu, Yifei; Shao, Mingmei; Xiang, Hongjiao; Wang, Junmin; Ji, Guang; Wu, Tao (Frontiers in Pharmacology, 2022)
Endoplasmic reticulum stress (ERS) plays a key role in alcohol liver injury (ALI). Lysophosphatidylcholine acyltransferase 3 (LPCAT3) is a potential modifier of ERS. It was examined whether the protective effect of Qinggan Huoxue Recipe (QGHXR) against ALI was associated with LPCAT3 by suppressing ERS from in vivo and in vitro experiment. Male C57BL/6 mice were randomly divided into five groups (n = 10, each) and treated for 8 weeks as follows: the control diet-fed group (pair-fed), ethanol diet-fed group (EtOH-fed), QGHXR group (EtOH-fed + QGHXR), Qinggan recipe group (EtOH-fed + QGR), and Huoxue recipe group (EtOH-fed + HXR). QGHXR, QGR, and HXR groups attenuated liver injury mainly manifested in reducing serum ALT, AST, and liver TG and reducing the severity of liver cell necrosis and steatosis in ALI mouse models. QGHXR mainly inhibited the mRNA levels of Lxrα, Perk, Eif2α, and Atf4 and activated the mRNA levels of Lpcat3 and Ire1α, while inhibiting the protein levels of LPCAT3, eIF2α, IRE1α, and XBP1u and activating the protein levels of GRP78 to improve ALI. QGR was more inclined to improve ALI by inhibiting the mRNA levels of Lxrα, Perk, Eif2α, Atif4, and Chop and activating the mRNA levels of Lpcat3 and Ire1α while inhibiting the protein levels of LPCAT3, PERK, eIF2α, IRE1α, and XBP1u. HXR was more inclined to improve ALI by inhibiting the mRNA levels of Perk, Eif2α, Atf4, and Chop mRNA while inhibiting the protein levels of LPCAT3, PERK, eIF2α, IRE1α, and XBP1u and activating the protein levels of GRP78. Ethanol (100 mM) was used to intervene HepG2 and AML12 to establish an ALI cell model and treated by QGHXR-, QGR-, and HXR-medicated serum (100 mg/L). QGHXR, QGR, and HXR groups mainly reduced the serum TG level and the expression of inflammatory factors such as IL-6 and TNF-α in the liver induced by ethanol. In AML12 cells, QGHXR and its disassembly mainly activated Grp78 mRNA expression together with inhibiting Lxrα, Lpcat3, Eif2α, Atf4, and Xbp1 mRNA expression. The protein expression of eIF2α and XBP1u was inhibited, and the expression of PERK and GRP78 was activated to alleviate ALI. In HepG2 cells, QGHXR mainly alleviated ALI by inhibiting the mRNA expression of LPCAT3, CHOP, IRE1α, XBP1, eIF2α, CHOP, and IRE1α protein. QGR was more inclined to inhibit the protein expression of PERK, and HXR was more likely to inhibit the protein expression of ATF4.